Variable flow pipework systems : valve solutions, supplement to CIBSE knowledge series KS7 - Parsloe, C. (Chartered Institution Of Building Services Engineers, 2009)
This publication forms a supplement to CIBSE Knowledge Series KS7: Variable flow pipework systems (CIBSE, 2006). It explains how to design re-circulating heating and cooling water systems incorporating variable speed pumps utilising two alternative valve solutions not covered in KS7, these being centralised valve modules and pressure independent control valves (PICVs).